Design and Analysis of Single Switch Double Enhanced Boost Converter for PV Applications - Ramprasath S.; Krishnakumar C. (ITM Web of Conferences, 2023)
This paper presents a systematic and analytical investigation of the non-isolated Single Switch Double Enhanced Boost Converter topology. In simple words combination of a DEC (Double Enhanced Circuit) With an ordinary boost converter. The proposed converter implements the output voltage increasing in geometric progression but with a simpler structure. There is one switch S, n inductors, (n + 2) capacitors, and (2n + 1) diodes in each circuit of the additional series. They also effectively enhance the voltage transfer gain in the power law. Steady-state equations were derived to examine the behaviour of the proposed converter. The proposed converter was designed for 100 W and simulated in MATLAB/Simulink, the simulation results demonstrate its effectiveness in terms of improved efficiency, reduced voltage stress, and enhanced power delivery to the load.